Exploring the Coupling of Land Development Intensity and Green Economy Development in the Pearl River Delta: Patterns, Challenges, and Strategic Pathways - Huiming Huang; Shuangyu Xu; Kailun Fang (Land)
This study investigates the spatiotemporal patterns of land development intensity and green economy development at the district and county level in nine cities within the Pearl River Delta (PRD). A comprehensive evaluation framework is developed using a coupling coordination degree model and panel vector autoregression (PVAR) model to explore the spatial and temporal evolution of their relationship. The research reveals several key findings. (1) In 2013–2023, land development intensity followed a pattern of “concentration in the east and south, and sparsity in the west and north”, highlighting significant regional imbalances. (2) In 2013–2023, high-intensity development areas tended to cluster together, forming high-value zones, while low-intensity areas were often located next to similarly underdeveloped regions, reflecting a “low-value connection” trend. (3) There is a long-term stable co-integration relationship between land development intensity and green economy development. This study fills a gap in research at the district and county scale and offers practical insights for optimizing regional growth strategies and fostering green economic development across different areas in 2013–2023. These findings contribute to the design of balanced and sustainable development policies in the PRD, addressing both economic growth and environmental sustainability.